2020
DOI: 10.3390/w12051470
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Water Surface Area of the Lake in the Steppe Region of Mongolia: A Case Study of Ugii Nuur Lake, Central Mongolia

Abstract: The Ugii Nuur Lake is not only one of the small hydrologically closed lakes located in the Orkhon River Basin in Central Mongolia but also the most vulnerable area for global climate change. Therefore, this study aims to investigate the impacts of recent global climate change on the water surface area. The data we analyzed were various measured hydro-meteorological variables of the lake basin and the lake surface area, which was estimated from Landsat series satellite data from 1986 to 2018. The methods we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…An analysis of ten lakes with considerable importance in Turkey showed a decrease in the surface area of nine of them, reaching 81% in the years 1985-2022 [20]. Research on changes in the surface area of Lake Ugii Nuur (Mongolia) showed that in the period of 1986-2018 it decreased by 13.5%, and the primary hydrometeorological factors determining the situation included evaporation and river outflow [43]. Wine et al [44] determined that agriculture and changes in the direction of water flow were the main factors causing the substantial shrinking of Lake Kinneret.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of ten lakes with considerable importance in Turkey showed a decrease in the surface area of nine of them, reaching 81% in the years 1985-2022 [20]. Research on changes in the surface area of Lake Ugii Nuur (Mongolia) showed that in the period of 1986-2018 it decreased by 13.5%, and the primary hydrometeorological factors determining the situation included evaporation and river outflow [43]. Wine et al [44] determined that agriculture and changes in the direction of water flow were the main factors causing the substantial shrinking of Lake Kinneret.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of temperature and precipitation was determined by the slope method. Q i is the slope between 2 datapoints and is determined as follows [34,35]:…”
Section: Sen's Slope Estimator Testmentioning
confidence: 99%
“…Davaa et al (2018) identified the possibility of assessing water resources of Mongolia's lakes and monitoring them regularly. Their study notes that the water level in the lakes has been steadily declining in recent years, based on ground and satellite data, and have recommended that further research is needed to determine the water resources of Mongolia's lakes [29][30].…”
Section: Lake Research Starting In the 1990smentioning
confidence: 99%